THE IMPACT OF LEARNENGLISH GRAMMAR APPLICATION ON GRAMMAR MASTERY AND STUDENTS’ PERCEPTIONS AT MTS MUHAMMADIYAH METRO - Anna Ihtida Haqqun; Dedi Turmudi; Refai (English Education Study Program, 2026)
This research aims to investigate the impact of the LearnEnglish Grammar application on eighth-grade students' grammar mastery at MTs Muhammadiyah Metro, identify any significant differences between students taught using the application and those taught through conventional methods, and explore students' perceptions of the application. Employing a quantitative approach with a quasi-experimental design, the study involved two groups: an experimental group using the application and a control group receiving traditional instruction. Cluster random sampling was used to select class 8B as the experimental group and class 8C as the control group, each consisting of 14 students. Data were collected through pre-tests, post-tests, and questionnaires. The results of the Paired Sample T-Test showed a significant improvement in grammar mastery within the experimental group (Sig. < 0.000), indicating a positive impact of the application. However, the Independent Sample T-Test results showed no significant difference between the two groups (Sig. = 0.057), indicating that learning with the traditional method provided comparable results to the app. The questionnaire results showed that students had a generally positive perception of the app, finding it useful, easy to use, and engaging. The findings conclude that LearnEnglish Grammar app enhances grammar learning although its effectiveness is comparable to conventional instruction, and future research is suggested to further investigate the use of LearnEnglish Grammar app with longer treatment duration and larger sample.